2020
DOI: 10.1021/acsomega.9b04468
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Bio-Oil and Nitrogen Recovery from Microalgae Using Two-Stage Hydrothermal Liquefaction with Solid Carbon and HCl Acid Catalysis

Abstract: Bio-oil production from microalgae by using hydrothermal liquefaction (HTL) has been conducted extensively in the last decade. In this work, we conducted two-stage HTL of a microalga (Fistulifera solaris, JPCC DA0580) in the presence of 5.0 g/L carbon solid acid or a 0.02−0.50 M HCl catalyst to increase bio-oil yield and nitrogen recovery into the aqueous phase (AP). The first stage (HTL 1), to hydrolyze proteins, carbohydrates, and lipids and elute nitrogen components into the AP, was conducted at 100−250°C f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 51 publications
(103 reference statements)
0
4
0
Order By: Relevance
“…24 Usami et al detected a decrease of amines and long-chain amine peaks in the biocrude converted from the microalga Fistulifera sp. when 0.50 M HCl was used by GC-MS. 25 Costanzo et al found a 30% reduction in N heteroatoms by low-temperature pretreatment by comparing chromatograms and semiquantitative GC-MS analysis using an internal standard. 26 Major amounts of fatty acid amides and Ncontaining heterocyclic compounds were observed in the biocrude converted from wet Chlorella sorokiniana and Dunaliella tertiolecta.…”
Section: Detecting and Analyzing Methodologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Usami et al detected a decrease of amines and long-chain amine peaks in the biocrude converted from the microalga Fistulifera sp. when 0.50 M HCl was used by GC-MS. 25 Costanzo et al found a 30% reduction in N heteroatoms by low-temperature pretreatment by comparing chromatograms and semiquantitative GC-MS analysis using an internal standard. 26 Major amounts of fatty acid amides and Ncontaining heterocyclic compounds were observed in the biocrude converted from wet Chlorella sorokiniana and Dunaliella tertiolecta.…”
Section: Detecting and Analyzing Methodologiesmentioning
confidence: 99%
“…Usami et al detected a decrease of amines and long-chain amine peaks in the biocrude converted from the microalga Fistulifera sp. when 0.50 M HCl was used by GC-MS . Costanzo et al found a 30% reduction in N heteroatoms by low-temperature pretreatment by comparing chromatograms and semiquantitative GC-MS analysis using an internal standard .…”
Section: Detecting and Analyzing Methodologies For Nitrogen Organic C...mentioning
confidence: 99%
“…Halder et al [62] showed 72%-76% of bio-oils were distilled in the range of 200 • C-550 • C by TG analysis, and it demonstrated the feasibility of applying HTL to produce bio-oil. Moreover, Usami et al [63] and Sharma et al [64] studied the performance between homogeneous and heterogeneous catalysts to improve the production of bio-oil in hydrothermal carbonization. Rapid pyrolysis for bio-oil production was a process in which the biomass was thermochemically transformed by a rapid temperature increase to 450 • C-600 • C under anoxic conditions.…”
Section: Bio-oilmentioning
confidence: 99%
“…With rapid population growth, increased consumer demand, and economic activity, the massive consumption of energy has led to many environmental problems, including global warming, acid rain, ocean pollution, and so on. Therefore, exploring sustainable and clean alternative energy has become an important theme of current social development. At present, biomass has attracted more attention and the conversion technology have moved from laboratory to industrial applications. , However, the bio-oil obtained through biomass thermal treatment contains many heteroatoms (such as O, N, S, etc. ), which leads to the poor properties of bio-crude. For instance, high oxygen content (35–40%) in bio-oils made from lignocellulosic biomass will result in low energy density, acidity, and low chemical stability. In addition, some bio-oils produced from algal biomass contain high levels of nitrogen-containing compounds (4.8–8.8%), which lead to molecular oligomerization, viscosity, and emission of nitrogen oxides during combustion. Therefore, in order to obtain high-quality fuel properties, it is necessary to remove most of the oxygen and nitrogen from the bio-oil.…”
Section: Introductionmentioning
confidence: 99%